Robust set stabilization of Boolean control networks with impulsive effects - Xu, Xiaojing; Liu, Yansheng; Li, Haitao; Alsaadi, Fuad E. E. (Nonlinear Analysis: Modelling and Control, 2018)
This paper addresses the robust set stabilization problem of Boolean control networks (BCNs) with impulsive effects via the semi-tensor product method. Firstly, the closed-loop system consisting of a BCN with impulsive effects and a given state feedback control is converted into an algebraic form. Secondly, based on the algebraic form, some necessary and sufficient conditions are presented for the robust set stabilization of BCNs with impulsive effects under a given state feedback control and a free-form control sequence, respectively. Thirdly, as applications, some necessary and sufficient conditions are presented for robust partial stabilization and robust output tracking of BCNs with impulsive effects, respectively. The study of two illustrative examples shows that the obtained new results are effective.
Keywords: Boolean control network; impulsive effects; set stabilization; robust control; semi-tensor product of matrices